Marcille school in « del Carrousel’s collection». Dupuis’children illustrated books (1966 - 1971) - Bozard, Laurent (Ondina - Ondine, 2023)
Between 1966 and 1971, the Belgian publisher Dupuis published a collection of children’s books that relied mostly on in-house scriptwriters and illustrators, most of whom were representatives of the “Marcinelle school”. If these great names of the 9th art still resonate today in the minds of comic book fans, the Carrousel albums cannot be truly qualified as «classics». In this contribution, we will identify the characteristics of this collection: its origin, its links with the 9th art and comics, the components of the collection (adaptation, creation, translation, transmedia, first readings). Then, we will approach the materiality of these albums by analyzing their adaptation to the iconotextual format of the children’s album, their relationship with the tales, the role of the illustration and the text specific to the album, the links with television. Finally, the last part of the study will deal with the question of the classicism of these works: accessibility, conservation, bibliophily, publishing, audiences and receptions. Key words: Carrousel’s collection, Dupuis, transmedia, 9th art, Marcinelle school.